2008
DOI: 10.1242/dev.025189
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblast entry into quiescence is regulated intrinsically by the combined action of spatial Hox proteins and temporal identity factors

Abstract: Neural stem cell quiescence is an important feature in invertebrate and mammalian central nervous system development, yet little is known about the mechanisms regulating entry into quiescence, maintenance of cell fate during quiescence, and exit from quiescence. Drosophila neural stem cells (called neuroblasts) provide an excellent model system for investigating these issues. Drosophila neuroblasts enter quiescence at the end of embryogenesis and resume proliferation during larval stages; however, no single ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 53 publications
7
141
0
3
Order By: Relevance
“…Third, ABLKs are the unique cells expressing Lk in the ventral ganglion. However, we have not observed downregulation of cas in nab mutants, and the same has been reported in the better characterized lineages of NB3-3 and NB5-6 (Baumgardt et al, 2009;Tsuji et al, 2008); together, these results indicate that the molecular relationship between Cas and Nab requires a more complex interpretation than a linear genetic cascade.…”
Section: A Genetic Cascade Involving Cas and Nab Specifies Ablk Neurosupporting
confidence: 88%
See 2 more Smart Citations
“…Third, ABLKs are the unique cells expressing Lk in the ventral ganglion. However, we have not observed downregulation of cas in nab mutants, and the same has been reported in the better characterized lineages of NB3-3 and NB5-6 (Baumgardt et al, 2009;Tsuji et al, 2008); together, these results indicate that the molecular relationship between Cas and Nab requires a more complex interpretation than a linear genetic cascade.…”
Section: A Genetic Cascade Involving Cas and Nab Specifies Ablk Neurosupporting
confidence: 88%
“…Recently, part of the underlying genetic mechanism controlling such temporal transitions in progenitor competence has been revealed (Brody and Odenwald, 2000;Cleary and Doe, 2006;Grosskortenhaus et al, 2005;Grosskortenhaus et al, 2006;Isshiki et al, 2001;Kambadur et al, 1998;Novotny et al, 2002;Pearson and Doe, 2003;Tran and Doe, 2008;Tsuji et al, 2008). These studies have identified the temporal identity genes, which are sequentially expressed in the NB and act to specify temporal windows in which the different GMCs are produced.…”
Section: During Development Of the Central Nervous Systems (Cns) Of Vmentioning
confidence: 99%
See 1 more Smart Citation
“…pCC, EW1-EW3, Apterous+ neurons and Eve+ lateral interneurons (Doe et al, 1988;Higashijima et al, 1996;Park et al, 2004;Thomas et al, 1984;Tsuji et al, 2008). The eNeuro atlas expands the number of identified interneurons to 958, each of which has been assigned a unique name, and each of which is described by quantitative information on cell body position, size and frequency of appearance, as well as its Gal4 line expression profile (supplementary material Data File S8).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental G2 phase arrest mediated by inhibitory phosphorylation of the Cdk1 mitotic regulator is an important mechanism for coordinating these processes in neural precursor cells O'Farrell, 1989, 1990). Precisely how G2 phase arrest contributes to neural development remains unclear (Tsuji et al, 2008).…”
Section: Introductionmentioning
confidence: 99%